A Practical Guide to Human Cancer Genetics - Hodgson, Shirley V.; Foulkes, William D.; Eng, Charis; Maher, Eamonn R.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
A Practical Guide to Human Cancer Genetics, 4th edition, is a comprehensive and up-to-date guide to the diagnosis, clinical features and management of inherited disorders conferring cancer susceptibility. This fully updated new edition covers risk analysis and genetic counseling for individuals with a family history of cancer, and includes a discussion of predictive testing and the organisation of the cancer genetics service. There is also information about the genes causing Mendelian cancer predisposing conditions and their mechanisms of action. This book is an invaluable reference source for students, general practitioners, geneticists and specialist clinicians in all disciplines.
1. Central Nervous System -- 2. Eye -- 3. Cardiorespiratory System and Thorax -- 4. Endocrine System -- 5. Gastrointestinal System -- 6. Reproductive System -- 7. Urinary System -- 8. Blood and Lymph -- 9. Musculoskeletal System -- 10. Skin -- 11. Inherited Cancer-Predisposing Syndromes.
Keywords: Medicine; Oncology; Human genetics; Medicine & Public Health; Oncology; Human Genetics; Cancer Research